KORELASI HASIL BELAJAR IPA SISWA DENGAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI LUBUKLINGGAU - Wahyu Arini (Jurnal Perspektif Pendidikan, 2022)
This research aims to determine whether there is a significant relationship between learning outcomes and motivation to study science subjects in class VIII students of SMP Negeri 7 Lubuklinggau. The research population was all students of class VIII SMP Negeri 7 Lubuklinggau consisting of 6 classes totaling 163 students and the research sample was class VIII1 students with a total of 27 students. The data analysis technique used in this research is the product moment correlation technique. Based on the results of the study it was found that as many as 20 students answered that their learning motivation was sufficient, and there were 16 students whose learning outcomes were classified as very good. The existence of a relationship between learning motivation and learning outcomes is proven by obtaining an rxy of 0,599 which is greater than rtable at a significant level of 5% = 0,382 So that rxy > rtable is obtained, namely 0,599 > 0,382 which is in the medium category. Then the t test was carried out, and ttable = 2,060 and tcount 3,733 were obtained. tcount > ttable so that Ho is rejected and Ha is accepted. This shows "there is a relationship between learning motivation and science learning outcomes for class VIII students of SMP Negeri 7 Lubuklinggau".